HR system and work ethics: A systematic review - Addisalem Tadesse Bogale; Zerihun Ayenew Birbirsa (Cogent Business & Management, 2023)
Human resource (HR) managers can provide significant value to their organizations by understanding the practices that develop HR systems, as well as the ethical implications of the work environment. However, there is a gap in the literature regarding the linkages between HR systems and ethical practices that govern workplace conduct. This study aims to fill this gap by demonstrating how past research has integrated HR systems and work ethics. We used a systematic literature review method to analyze the development of the field over the last decade. To synthesize a fragmented body of research and map out its relationships into a more integrated whole, we reviewed and analyzed 47 articles that met the selection criteria and extracted important information. Based on the findings, the relationships between HR systems and employee well-being are viewed from two contradictory points of view: mutual gain and a critical perspective. Our review also found that failing to adhere to ethical principles and values may result in numerous detrimental outcomes in the workplace, including poor performance, employee conflict, and a lack of moral conviction. Finally, we identified gaps in current knowledge and proposed actionable research directions to address these gaps in the literature.
Keywords: 650; HR bundles; HR practice; HR system; human resource management systems; review; work ethics